Thermal behavior, spectroscopic study and evolved gas analysis (EGA) during pyrolysis of picolinic acid, sodium picolinate and its light trivalent lanthanide complexes in solid state - Do Nascimento, A. L.C.S. [UNESP]; Teixeira, J. A. [UNESP]; Nunes, W. D.G. [UNESP]; Campos, F. X. [UNESP]; Treu-Filho, O. [UNESP]; Caires, F. J. [UNESP]; Ionashiro, M. [UNESP] (Elsevier, 2016)
Synthesis, characterization, and thermal behavior of light trivalent lanthanide picolinate (La-Gd, except Pm) as well as the thermal behavior of picolinic acid and its sodium salt were investigated employing elemental analysis, complexometry, differential scanning calorimetry (DSC), simultaneous thermogravimetry and differential scanning calorimetry (TG-DSC), infrared spectroscopy (FTIR), X-ray power diffractometry, and evolved gas analysis (EGA) for TG-DSC coupled to FTIR. All the synthesized compounds were obtained in the anhydrous state and the thermal decomposition in dynamic dry air atmosphere occured in a single step or two consecutive steps with formation of the respective oxides, CeO2, Pr6O11 and Ln2O3 (Ln = La, Nd to Gd). In dynamic dry nitrogen atmosphere the thermal decomposition occured in two or three consecutive steps and mass loss was observed up to 1000 °C. The EGA data allowed the identification of gaseous products evolved during pyrolysis and oxidative decomposition. The results of density functional theory (DFT) and FTIR also provided information on the ligand's denticity.
Keywords: Density functional theory (DFT); Evolved gases analysis (EGA); Light trivalent lanthanides; Picolinate; Pyrolysis